Evolutionary history and structure of nuclear matrix constituent proteins, the plant analogues of lamins - Ciska, Malgorzata (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.